Parametres of Fountain Pen Ink Using Common Alder (Alnus glutinosa L. gaertn) Leaves by Fermentation Method - KAVAK, FERDA; ONAL, ADEM (Asian Journal of Chemistry, 2010)
Formation of gallic acid from common alder (Alnus glutinosa L. gaertn) leaves has been carried out by fermentation method. FeSO4 was added to form black complex used as fountain pen ink after addition of gum to adjust the viscosity of the ink. Some physical parameters of the common alder ink such as viscosity, density, drying time and pH were investigated and these properties were compared with two commercial inks.